MULTI-STAGES OPTIMIZED PHOTOIONIZATION MODELLING OF PLANETARY NEBULA LMC SMP-21 - Melekh, B. Ya.; Holovatyy, V. V.; Havrylova, N. V.; Sokil, M. M.; Tyshko, N. L.; Demchyna, A. V. (Одеські астрономічні публікації, 2012)
The new approximation expression for the representation of gas density distribution in planetary nebulae envelopes was proposed. The new multi-stages method for the caclulation of the chemical composition and physical parameters of planetary nebulae envelopes based on the optimized photoionization modelling was described. This method was used to the determination of physical characteristics and chemical composition in PN LMC SMP-21.